Hubungan Metode Bercerita dengan Karakter Siswa Di Madrasah Ibtidaiyah Negeri 1 Purbalingga - Siti Mangunah (LPPM IAINU Kebumen, 2020)
This research is based on the importance of character in creating a young generation with good character. In this regard, this study aims to determine the relationship between the storytelling method and the character of students at MIN 1 Purbalingga. This study uses a quantitative research approach. While the type of research used in this research is a quasi-experimental design or quasi-experimental design. The experimental design used in this study was a